The Portuguese version of the body investment scale: psychometric properties and relationships with disordered eating and emotion dysregulation - Vieira, Ana Isabel (2020)
Background This study aimed to examine the psychometric properties of the Portuguese version of the Body Investment Scale (BIS) in a nonclinical sample of students and a clinical sample of outpatients with eating disorders, to analyse the differences in the BIS factors between the samples and to explore the relationships among body investment, eating disorder symptoms and difficulties in emotion regulation. Methods The clinical (n = 93) and nonclinical (n = 448) samples completed self-report measures. Results In contrast to the nonclinical sample, confirmatory factor analysis showed an acceptable fit for the original four-factor solution of the BIS in the clinical sample. This scale also demonstrated adequate internal consistency in both samples. Significant differences in BIS factors were found between the samples; outpatients with eating disorders presented more negative feelings about the body, less comfort with touch and lower levels of body protection than those of the students. In the clinical sample, significant relationships were found between these factors and a higher severity of disordered eating, as well as between these factors and higher difficulties in emotion regulation. Conclusions The Portuguese version of the BIS is a psychometrically sound measure for the assessment of body investment, and it is especially appropriate in a clinical setting of outpatients with eating disorders.